2023
DOI: 10.1186/s12974-023-02697-x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal inflammation increases hippocampal KCC2 expression through methylation-mediated TGF-β1 downregulation leading to impaired hippocampal cognitive function and synaptic plasticity in adult mice

Abstract: The mechanisms by which neonatal inflammation leads to cognitive deficits in adulthood remain poorly understood. Inhibitory GABAergic synaptic transmission plays a vital role in controlling learning, memory and synaptic plasticity. Since early-life inflammation has been reported to adversely affect the GABAergic synaptic transmission, the aim of this study was to investigate whether and how neonatal inflammation affects GABAergic synaptic transmission resulting in cognitive impairment. Neonatal mice received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…LTP is the most widely used paradigm to study molecular and cellular events underlying synaptic transmission and is considered a putative mechanism for learning and memory (Bliss & Collingridge, 1993). Impaired LTP at the hippocampal synapses is a potential neurobiological mechanism underlying cognitive impairment, as learning and memory deficits are commonly observed in animals with impaired LTP (Rong et al, 2023; Zhu et al, 2022). Several natural products and derived compounds have been reported to alleviate cognitive impairment by repairing impaired LTP (Choi et al, 2023; Park et al, 2021; Wang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LTP is the most widely used paradigm to study molecular and cellular events underlying synaptic transmission and is considered a putative mechanism for learning and memory (Bliss & Collingridge, 1993). Impaired LTP at the hippocampal synapses is a potential neurobiological mechanism underlying cognitive impairment, as learning and memory deficits are commonly observed in animals with impaired LTP (Rong et al, 2023; Zhu et al, 2022). Several natural products and derived compounds have been reported to alleviate cognitive impairment by repairing impaired LTP (Choi et al, 2023; Park et al, 2021; Wang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…(d) Root mean squared deviation (RMSD) and (e) root mean squared fluctuation (RMSF) line plots of the PI3K-Pra-C complex during 200 ps stimulation.putative mechanism for learning and memory(Bliss & Collingridge, 1993). Impaired LTP at the hippocampal synapses is a potential neurobiological mechanism underlying cognitive impairment, as learning and memory deficits are commonly observed in animals with impaired LTP(Rong et al, 2023;Zhu et al, 2022). Several natural products and derived compounds have been reported to alleviate F I G U R E 6 Praeruptorin C (Pra-C) restored PI3K/AKT/GSK3β signaling pathway in the hippocampus.…”
mentioning
confidence: 99%
“…However, recent investigations have shown that the opposite regulation can also be detrimental and that excessive GABAA-mediated inhibition due to hypernegative current reversal potential represents another potential mechanism of pathology. For example, adult mice that were exposed to neonatal inflammation (using an LPS injection) show cognitive impairments associated with hypernegative GABAA reversal potential and increased KCC2 activity in the hippocampus [79]. Interestingly, these authors showed a complex TGF-β1-dependent regulation, suggesting the alteration is not simply due to an overdrive of the normal developmental KCC2 upregulation.…”
Section: Hypernegative Gabaa Currentmentioning
confidence: 99%